A 1D Vanadium Dioxide Nanochannel Constructed via Electric‐Field‐Induced Ion Transport and its Superior Metal–Insulator Transition. Issue 39 (21st August 2017) - Xue, Wuhong; Liu, Gang; Zhong, Zhicheng; Dai, Yuehua; Shang, Jie; Liu, Yiwei; Yang, Huali; Yi, Xiaohui; Tan, Hongwei; Pan, Liang; Gao, Shuang; Ding, Jun; et al.
Abstract: Nanoscale manipulation of materials' physicochemical properties offers distinguished possibility to the development of novel electronic devices with ultrasmall dimension, fast operation speed, and low energy consumption characteristics. This is especially important as the present semiconductor manufacturing technique is approaching the end of miniaturization campaign in the near future. Here, a superior metal–insulator transition (MIT) of a 1D VO2 nanochannel constructed through an electric‐field‐induced oxygen ion migration process in V2 O5 thin film is reported for the first time. A sharp and reliable MIT transition with a steep turn‐on voltage slope of <0.5 mV dec −1, fast switching speed of 17 ns, low energy consumption of 8 pJ, and low variability of <4.3% is demonstrated in the VO2 nanochannel device. High‐resolution transmission electron microscopy observation and theoretical computation verify that the superior electrical properties of the present device can be ascribed to the electroformation of nanoscale VO2 nanochannel in V2 O5 thin films. More importantly, the incorporation of the present device into a Pt/HfO2 /Pt/VO2 /Pt 1S1R unit can ensure the correct reading of the HfO2 memory continuously for 10 7 cycles, therefore demonstrating its great possibility as a reliable selector in high‐density crossbar memory arrays. Abstract : A 1D vanadium dioxide nanochannel is constructed via electric‐field‐induced ion transport and a related solid‐state redox reaction in V2 O5 thin film. A superior metal–insulator transition of VO2 with sharp transition, fast switching speed, low energy consumption, and excellent reproducibility is demonstrated. The VO2 nanostructure can act as a promising candidate for the selector element in high‐density crossbar memory arrays.